Participatory urban adaptation to climate change: A guide for the effective collaboration of local governments and city residents - Rzeńca, Agnieszka; Boryczka, Ewa; Burlińska, Agata; Brzeziński, Kamil; Jurczak, Tomasz; Kamińska, Klaudia; Krzewińska, Aneta; Nowakowska, Aleksandra; Wasiak, Anna (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
Participatory urban adaptation to climate change, as was shown in the Guide, is a complex endeavour whose success relies on openness to change, and the cooperation of many entities, both in developing an attitude toward adapting cities to climate change and using deliberative techniques for this purpose. In this process, it is equally important to exchange experiences and share knowledge on successes and challenges in using participatory techniques, along with their potential and limitations. As the authors, we hope that the Guide will draw you to participatory urban adaptation to climate change and encourage and motivate you to implement the techniques and methods presented for creating an urban climate policy. This, in turn, will make it possible to master this process in practice, modify and update it, and implement new solutions. At this point, we would like to extend our heartfelt acknowledgements and gratitude to the local governments and members of the Town Halls in Poland, Hungary and Slovakia, members of non-governmental organisations and academic centres in Banská Bystrica, Trnava, Miskolc and Budapest for their time, valuable comments, suggestions and endless discussions on how to better solve their cities’ problems by engaging the potential of their residents.